Are Amyloid Fibrils RNA-Traps? A Molecular Dynamics Perspective - Meli, Massimiliano; Gasset, Maria; Colombo, Giorgio (Frontiers in Molecular Biosciences, 2018)
The self-assembly of proteins and peptides into amyloids is a key feature of an increasing number of diseases. Amyloid fibrils display a unique surface reactivity endowing the sequestration of molecules such as MicroRNAs, which can be the active moiety of the toxic action. To test this hypothesis we studied the recognition between a model RNA and two different steric zipper spines using molecular dynamics simulations. We found that the interaction occurs and displays peptide-sequence dependence. Interestingly, interactions with polar zipper surfaces such as the formed by SNQNNF are more stable and favor the formation of β-barrel like complexes resembling the structures of toxic oligomers. These sequence-structure-recognition relationships of the two different assemblies may be exploited for the design of compounds targeting the fibers or competing with RNA-amyloid attachment